A Pragmatic Study of Family-Theme Swearing Used in Compliments on Twitter - Aprilia Kartika Putri; Oktavianus Oktavianus; Rina Marnita (STKIP Singkawang, 2019)
Swearing is deemed as improper to use in certain settings. However, it can be used to convey positive emotions too, including complimenting something or someone. This research article aims to investigate the linguistic forms, pragmatic meanings, and pragmatic functions of family-theme swearing used in compliments on Twitter. Kreidler (2002), Ramlan (2005), and Ljung (2011)’s opinions were utilized in this research. Observational method was used to collect the data. Distributional and identity method were used to analyze the data. The results of this study demonstrate that: (1) linguistic forms of family-theme swearing are word and phrase, (2) the pragmatic meaning of the family-theme swearing is as utterance meaning, and (3) the pragmatic functions of the family-theme swearing are as Adjectival Intensifier and Anaphoric Use of Epithets. This research is hopefully able to assist EFL (English as a Foreign Language) students to communicate in English better with other English speakers on Twitter.